2000
DOI: 10.1111/j.1349-7006.2000.tb01029.x
|View full text |Cite
|
Sign up to set email alerts
|

No Association of the 5′Promoter Region Polymorphism of CYP17 with Breast Cancer Risk in Japan

Abstract: To examine the association between breast cancer risk and a T-to-C substitution polymorphism at the 5′ ′ ′ ′ promoter region of CYP17, a case-control study was conducted at Aichi Cancer Center Hospital in Japan. Subjects were 144 histologically confirmed breast cancer patients diagnosed in the past 4 years and 166 hospital controls without cancer. Allele frequency among controls was 44.9% (95% confidence interval; 39.5-50.2) for C allele. Odds ratio (OR) of the polymorphism relative to TT-genotype was 0.97 (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…Several studies have found a positive association between A2/A2 genotype and the risk of breast cancer in the subgroups such as younger (22-36 years old) Sweden (Bergman-Jungestrom et al, 1999), younger ( 40) Australian (Spurdle et al, 2000) and older ( 55) Japanese (Miyoshi et al, 2000). However, most other studies could not reproduce the positive association between A2/A2 genotype and breast cancer risk; e.g., no association was found in studies conducted for Caucasians in UK (Dunning et al, 1998), US (Weston et al, 1998;Haiman et al, 1999;Ambrosone et al, 2003), Finland (Mitrunen et al, 2000), hispanics and African-Americans in US (Weston et al, 1998), Japanese (Hamajima et al, 2000), Chinese in Singapore (Wu et al, 2003) and Taiwanese (Huang et al, 1999).…”
Section: Genetic Polymorphism Of Cyp17 and Breast Cancer Risk In Korementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found a positive association between A2/A2 genotype and the risk of breast cancer in the subgroups such as younger (22-36 years old) Sweden (Bergman-Jungestrom et al, 1999), younger ( 40) Australian (Spurdle et al, 2000) and older ( 55) Japanese (Miyoshi et al, 2000). However, most other studies could not reproduce the positive association between A2/A2 genotype and breast cancer risk; e.g., no association was found in studies conducted for Caucasians in UK (Dunning et al, 1998), US (Weston et al, 1998;Haiman et al, 1999;Ambrosone et al, 2003), Finland (Mitrunen et al, 2000), hispanics and African-Americans in US (Weston et al, 1998), Japanese (Hamajima et al, 2000), Chinese in Singapore (Wu et al, 2003) and Taiwanese (Huang et al, 1999).…”
Section: Genetic Polymorphism Of Cyp17 and Breast Cancer Risk In Korementioning
confidence: 99%
“…A number of epidemiological studies have evaluated the potential role of CYP17 polymorphism in breast cancer development (Feigelson et al, 1997;Dunning et al, 1998;Helzlsouer et al, 1998;Weston et al, 1998;Bergman-Jungestrom et al, 1999;Huang et al, 1999;Hamajima et al, 2000;Kuligina et al, 2000;Mitrunen et al, 2000;Miyoshi et al, 2000;Spurdle et al, 2000;Ambrosone et al, 2003;Cui et al, 2003;Wu et al, 2003;Hefler et al, 2004) since the first association study (Feigelson et al, 1997) reported that A2 carriers had 2.5-fold higher risk of advanced breast cancer in a nested case-control study of multiethnic cohort. However, the results for the association between CYP17 polymorphism and breast cancer risk have been inconsistent.…”
Section: Genetic Polymorphism Of Cyp17 and Breast Cancer Risk In Korementioning
confidence: 99%
“…14 In contrast, CYP17 genotype was not associated with breast cancer risk in other studies conducted in the US, 14 -16 United Kingdom, 17 Norway, 18 Finland, 19 Russia 20 and Japan. 21 High endogenous estrogen levels in association with the A2 allele have been reported, 16,22 although more recent data suggest that the association may be relatively weak. 23 The inconsistent findings in relation to this CYP17 polymorphism and, more importantly, the inadequacy of studying single genes one at a time 24 led to the investigations of other genes in conjunction with CYP17 that are involved in the biosynthesis and metabolism of estrogens.…”
mentioning
confidence: 99%
“…While some authors suggested that the CYP17 A2 allele was associated with an increased risk of the disease 24 others reported no difference in the distribution of the different alleles among healthy and breast cancer patients. 16,25 The strong experimental evidence that the T to C substitution does not create a binding site for Sp-1 16 refutes the hypothesis that the CYP17 A2 would be the risk allele and suggest that these genotypes alone are of little value for breast cancer risk estimation. 25 …”
Section: Discussionmentioning
confidence: 93%
“…16,25 The strong experimental evidence that the T to C substitution does not create a binding site for Sp-1 16 refutes the hypothesis that the CYP17 A2 would be the risk allele and suggest that these genotypes alone are of little value for breast cancer risk estimation. 25 …”
Section: Discussionmentioning
confidence: 93%